Software for the Linesman Radar Data Processing System. (3rd October 2018) - Pyle, Ian C
Abstract: Before we had the Internet, computers rarely cooperated with one another. In the 1970s, over a dozen closely connected computers processed the radar data for the UK's Air Defence system. Some of the techniques used then were described in 1972, without disclosing the context. Many years after the decommissioning and replacement of that system, we can now describe the software that made it work. Innovative principles and strategies were used to produce a large multi-computer software system. In practice, the infrastructure was much larger than the application software; and the experience gained was more about computer systems than about radar. As well as describing the software concerned, we identify the significant influences on it, and the benefits that were achieved from it.